2007
DOI: 10.1111/j.1467-9701.2007.01031.x
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Factors Influencing the Anti‐dumping Behaviour in India

Abstract: The use of anti-dumping measures as a trade protection tool, has increased phenomenally during the last decade. One significant aspect of this new trend is the increasing involvement of developing countries. India is one such country which has emerged as a very frequent user of anti-dumping measures, surpassing even the traditional users. It had initiated more than 300 anti-dumping cases by the end of 2002-03. Many of these cases are against developing countries. Most of the cases are concentrated in narrow ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In a study on anti-dumping use in India, Bown and Tovar (2010) empirically examined the relationship between import tariff cuts and the subsequent use of anti-dumping at the product-level in India. Their results showed that the products with larger tariff cuts between 1990 and 1997 were associated with the use of anti-dumping in the early 2000s in a statistically significant manner (see Baruah 2007). Increased use of AD with trade liberalization is not unexpected as the primary objective of anti-dumping is to mitigate the adverse effects of free trade (Aggarwal 2004;Feinberg & Raynold 2007;Moore & Zanardi 2009).…”
Section: What Makes India An Interesting Case For the Analysis?mentioning
confidence: 88%
“…In a study on anti-dumping use in India, Bown and Tovar (2010) empirically examined the relationship between import tariff cuts and the subsequent use of anti-dumping at the product-level in India. Their results showed that the products with larger tariff cuts between 1990 and 1997 were associated with the use of anti-dumping in the early 2000s in a statistically significant manner (see Baruah 2007). Increased use of AD with trade liberalization is not unexpected as the primary objective of anti-dumping is to mitigate the adverse effects of free trade (Aggarwal 2004;Feinberg & Raynold 2007;Moore & Zanardi 2009).…”
Section: What Makes India An Interesting Case For the Analysis?mentioning
confidence: 88%
“… Debapriya and Panda (2006) focus on India and China, Baruah (2007) on India, Francois and Niels (2004), Niels and Francois (2006) on Mexico, and Mah and Kim (2006) on Korea. …”
mentioning
confidence: 99%
“…First, the classification that we use is too aggregated to allow us to make such a distinction operational. Second, the bulk of antidumping initiations in developing countries involve intermediate products; for example, 78% of the initiations in 1987–2002 in Mexico (Reyes de la Torre and González 2005), and 92% over 1992–2003 in India (Baruah 2007).…”
mentioning
confidence: 99%